2017
DOI: 10.1007/s00520-017-3882-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of web-based interventions on cancer patients’ symptoms: review of randomized trials

Abstract: This review shows the promising potential of web-based interventions for cancer symptom management, although it was limited by considerable heterogeneity in the interventions tested and targeted outcomes. The multidimensional nature of symptoms was partly addressed; only one study was guided by a comprehensive theoretical model of cancer symptom management. It can only be speculated which web elements are important for effective symptom outcomes. Further testing is needed for web-based cancer symptom managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 65 publications
5
96
0
2
Order By: Relevance
“…Web‐based survivorship interventions have been shown to reduce anxiety and improving HRQoL among breast cancer patients . Fridriksdottir et al reported in their review that web‐based interventions positively affected anxiety, depression, and HRQoL for cancer patients who mostly were breast or female cancer survivors . Previous studies have indicated that website attributes, Internet usage patterns, and habits are different across genders .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Web‐based survivorship interventions have been shown to reduce anxiety and improving HRQoL among breast cancer patients . Fridriksdottir et al reported in their review that web‐based interventions positively affected anxiety, depression, and HRQoL for cancer patients who mostly were breast or female cancer survivors . Previous studies have indicated that website attributes, Internet usage patterns, and habits are different across genders .…”
Section: Discussionmentioning
confidence: 99%
“…28 HRQoL for cancer patients who mostly were breast or female cancer survivors. 9 Previous studies have indicated that website attributes, Internet usage patterns, and habits are different across genders. [29][30][31] The differences in the findings of our review and those from the other reviews suggest that the effects of TBIs may also vary by gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic health (eHealth) interventions, defined as "health services and information delivered or enhanced through the internet and related technologies" (1) , have shown promising results in providing patients with self-management support (2) , symptom management (3) , enabling online patientprovider communication, monitoring and shared decision making (4) . eHealth interventions have the potential to optimize health-related processes, reach a large number of people and achieve cost effectiveness (5) .…”
Section: Introductionmentioning
confidence: 99%